1999
DOI: 10.1524/ract.1999.87.12.47
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Radionuclides as Tracers in Terrestrial and Extraterrestrial Matter

Abstract: Environmental radioactivity / Cosmogenic radionuclides / Long-lived radionuclides / Accelerator mass spectrometry / Natural and mass-made tracers SummaryRadionuclides in nature offer unique opportunities for radioactive dating and tracing of natural and man-made processes. Naturally occurring radionuclides with half-lives between a few days and IO 12 a have found widespread applications some of which are surveyed here. After a short glance on radionuclide production in stellar nucleosynthesis and on extinct ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 118 publications
(256 reference statements)
0
8
0
Order By: Relevance
“…For the assessment of the extraterrestrial 26 Al fraction we measured Al and 53 Mn in meteorites and interplanetary dust (Reedy, 1990;Nishiizumi et al, 1995;Michel, 1999) Be ratio.…”
Section: Al/ 10mentioning
confidence: 99%
“…For the assessment of the extraterrestrial 26 Al fraction we measured Al and 53 Mn in meteorites and interplanetary dust (Reedy, 1990;Nishiizumi et al, 1995;Michel, 1999) Be ratio.…”
Section: Al/ 10mentioning
confidence: 99%
“…Field measurements and laboratory studies on iodine speciation using the long-lived radioactive 129 I isotope have contributed to our knowledge of the behaviour of iodine in the environment (Fabryka-Martin et al 1985;Behrens 1988;Michel 1999;Rädlinger andHeumann 2000, Moran et al 2002). In this context, it has been suggested that humic substances play a major role in converting and binding iodine in soils.…”
Section: Introductionmentioning
confidence: 99%
“…Cosmogenic radioactive and stable nuclides in chondrites have preserved important records of their exposure history during the last ten million years (e.g., Michel, 1999;Vogt et al, 1990;Caffee et al, 1988). For example, activity of typical neutron-capture product, 60 Co has been used as an indicator of their preatmospheric size (e.g., Eberhardt et al, 1963;Spergel et al, 1986), and those of spallation products, 22 Na, 54 Mn and 26 Al etc.…”
Section: Introductionmentioning
confidence: 99%